Investigational Treatment Agents for Recurrent Clostridioides difficile Infection (rCDI) - Kullar R; Tran MCN; Goldstein EJC (Dove Medical Press, 2020)
Ravina Kullar,1 Mai-Chi N Tran,2,3 Ellie JC Goldstein4,5 1Expert Stewardship, Inc., Newport Beach, CA, USA; 2Pharmacy Department, Keck Medical Center of USC, Los Angeles, CA, USA; 3Clinica Juan Pablo Medical Group, Los Angeles, CA, USA; 4R.M. Alden Research Laboratory, Santa Monica, CA, USA; 5David Geffen School of Medicine, Los Angeles, CA, USACorrespondence: Ellie JC Goldstein Tel +1-310-315-1511Email ejcgmd@aol.comAbstract: Clostridioides difficile infection (CDI) is a major cause of nosocomial diarrhea that is deemed a global health threat. C. difficile strain BI/NAP1/027 has contributed to the increase in the mortality, severity of CDI outbreaks and recurrence rates (rCDI). Updated CDI treatment guidelines suggest vancomycin and fidaxomicin as initial first-line therapies that have initial clinical cure rates of over 80%. Unacceptably high recurrence rates of 15– 30% in patients for the first episode and 40% for the second recurrent episode are reported. Alternative treatments for rCDI include fecal microbiota transplant and a human monoclonal antibody, bezlotoxumab, that can be used in patients with high risk of rCDI. Various emerging potential therapies with narrow spectrum of activity and little systemic absorption that are in development include 1) Ibezapolstat (formerly ACX-362E), MGB-BP-3, and DS-2969b-targeting bacterial DNA replication, 2) CRS3213 (REP3123)-inhibiting toxin production and spore formation, 3) ramizol and ramoplanin-affecting bacterial cell wall, 4) LFF-571-blocking protein synthesis, 5) Alanyl-L-Glutamine (alanylglutamine)-inhibiting damage caused by C. difficile by protecting intestinal mucosa, and 6) DNV3837 (MCB3681)-prodrug consisting of an oxazolidinone–quinolone combination that converts to the active form DNV3681 that has activity in vitro against C. difficile. This review article provides an overview of these developing drugs that can have potential role in the treatment of rCDI and in lowering recurrence rates.Keywords: Clostridioides difficile, CDI, C. difficile, C. difficile infection, investigational drugs